Sodium/proton antiporter in Streptococcus faecalis. - Kakinuma, Y (1987)
Streptococcus faecalis, like other bacteria, accumulates potassium ions and expels sodium ions. This paper is concerned with the pathway of sodium extrusion. Earlier studies (D.L. Heefner and F.M. Harold, Proc. Natl. Acad. Sci. USA 79:2798-2802, 1982) showed that sodium extrusion is effected by a primary, ATP-linked sodium pump. I report here that cells grown under conditions in which sodium ATPase is not induced can still expel sodium ions. This finding suggested the existence of an alternate pathway. Sodium extrusion by the alternate pathway requires the cells to generate a proton motive force. This conclusion rests on the following observations. (i) Sodium extrusion required glucose. (ii) Sodium extrusion was observed at neutral pH, which allows the cells to generate a proton motive force, but not at alkaline pH, which reduces the proton motive force to zero. (iii) Sodium extrusion was inhibited by the addition of dicyclohexylcarbodiimide and of proton-conducting ionophores. (iv) In response to an artificial pH gradient (with the exterior acid), energy-depleted cells exhibited a transient sodium extrusion which was unaffected by treatments that dissipated the membrane potential and which was blocked by proton conductors. I propose that streptococci have two independent systems for sodium extrusion: an inducible sodium ATPase and a constitutive sodium/proton antiporter.